THE ACCEPTANCE FACTORS FOR ISLAMIC BANKING FINTECH SEVICES: EXTENDED TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH - Lailatur Rohmah; Nurul Lailatul Mumtahanah; Evrina Ross Pratiwi (Universitas Airlangga, 2022)
Era 4.0 requires Islamic banking to optimize its services through digital platforms to make it easier for customers to transact. Indonesia is a large market for Islamic banking products, so Islamic banking should provide the best possible digital services and people will be more interested in using Islamic bank products. Therefore, it is necessary to analyze the factors that influence customers in using Islamic bank services online so that the quality of digital services can be improved. This study aims to determine the factors that influence the acceptance of Islamic bank customers for financial technology (Fintech) services in Indonesia by using the Extended Technology Acceptance Model (TAM) approach. The TAM model states that system users tend to use the system if the system is easy to use and useful for its users. Extended TAM adds a consumer innovation variable, namely the degree to which an individual is relatively earlier in adopting an innovation than other members of the system. This research is a type of quantitative research using primary and secondary data. Primary data was obtained from a survey of Islamic bank customers using convenience sampling. Secondary data is obtained from related literature sourced from journals, articles, books, and official government or banking websites. The results show that the acceptance of Islamic banking fintech services in Indonesia is determined by the perceived ease of use and customer innovation (consumer innovativeness), while the perceived usefulness does not affect the acceptance of Islamic bank customers for the use of mobile banking. This research will be useful as a reference for policymakers, academics, and researchers in the future.